Iron-Catalyzed Thiocyclization for the Synthesis of Trifluoromethylated Benzothiophenes by C–H Functionalization of Aryl Disulfides - Lin, Yan-Feng; Wang, Chong; Hu, Bo-Lun; Qian, Peng-Cheng; Zhang, Xing-Guo (Synlett, 2017)
An iron-catalyzed thiocyclization of propynols with aryl disulfides has been developed for the synthesis of trifluoromethylated benzothiophenes. The one-pot tandem reaction involves Meyer–Schuster rearrangement of propynols and radical cyclization through C–H functionalization of aryl disulfides. A variety of 2-trifluoroacyl benzothiophenes were prepared in moderate to good yields with good functional-group tolerance.
Keywords: annulations; C–H functionalization; iron; radical; trifluoromethyl